Fractional Fourier transform and stability of fractional differential equation on Lizorkin space - Unyong, Bundit; Mohanapriya, Arusamy; Ganesh, Anumanthappa; Rajchakit, Grienggrai; Govindan, Vediyappan; Vadivel, R.; Gunasekaran, Nallappan; Lim, Chee Peng (Advances in Difference Equations, 2020)
In the current study, we conduct an investigation into the Hyers–Ulam stability of linear fractional differential equation using the Riemann–Liouville derivatives based on fractional Fourier transform. In addition, some new results on stability conditions with respect to delay differential equation of fractional order are obtained. We establish the Hyers–Ulam–Rassias stability results as well as examine their existence and uniqueness of solutions pertaining to nonlinear problems. We provide examples that indicate the usefulness of the results presented.